A economia do nós: Uma perspectiva franciscana - Carbajo Núñez, Martín (Revista Eclesiástica Brasileira, 2022)
A visão franciscana da economia, que teve um notável desenvolvimento nos séculos XIII a XV, continua surpreendente atual. Reconheceu-o recentemente o Papa Francisco ao convocar, para Assis, um encontro mundial de jovens economistas, intitulado “A Economía de Francisco”, para promover um sistema econômico mais fraterno, atento aos pobres e ao meio-ambiente. Por causa da pandemia da Covid-19, o encontro aconteceu em forma on-line, de 19 a 21 de novembro de 2020. Este artigo apresenta os traços fundamentais da economia franciscana que o Papa quis propor como modelo inspirador para uma nova economia. Palabras-clave: Economia; Francisco de Assis; Papa Francisco; Franciscanos; Montes de Piedade. Abstract: The Franciscan vision of the economy**, which had a remarkable development during the 13th-15th centuries, keeps being relevant today. This fact has been recently recognized by Pope Francis when he convened a world meeting of young economists in Assisi, entitled “The economy of Francesco”, to promote a more fraternal economic system, more attentive to the poor and the environment. Because of the Covid-19 pandemic, the meeting ended up being held online on November 19-21, 2020. This article presents the fundamental features of the Franciscan economy that the Pope has once again proposed as an inspirational model for a new economy today. Keywords: Economy; Francis of Assisi; Pope Francis; Franciscans; Mounts of Piety.